Perbandingan Pandangan Ulama Fiqih Dalam Penetapan Ujrah Pada Akad Rahn Emas Di BPRS Authors Muhammad Isa - Isa, Muhammad; Adzkia, Nida (INSTITUT AGAMA ISLAM TAZKIA, 2018)
The question of an increase in the basic necessities of the community who wants to quickly fulfilled, the current lifestyle of luxury and convenience due to urgent need so that whatever is done to meet the necessities of life. Therefore in societies emerging practice moneylender or moneylenders, pawnshops illegal debt and usury. Then the unit services rahn gold in PT. BPRS Amanah Ummah Leuwiliang Bogor offers products rahn gold with gold rahn contract according Islamic law. Formulation of the problem in this research how the implementation contract rahn gold in BPRS Amanah Ummah PT. Leuwiliang, Bogor and whether the implementation contract rahn gold in BPRS Amanah Ummah PT. the determination of ujrah in accordance with the view of Hanafiyyah and Syafi’iyyah. The method of this research is qualitative research with the descriptive approach. The research data was obtained from the results of observations, interviews, and literature studies. This research is the contract rahn gold PT. BPRS Amanah Ummah implement three contract, such contract qard, contract ijarah and contract rahn. Determination of ujrah in practice at Bank rahn Amanah Ummah an ujrah of weight and gold levels warranted, because if ujrah adjusted to the amount of the loan then it is usury. Then based on the practice of the implementation contract rahn gold PT. BPRS Amanah Ummah in the determination of the imposition of ujrah have appropriate with the sect of Hanafiyyah and Syafi’iyyah.